Square lithium ion battery
By using excellent positive and negative electrode film forming additives and short-chain carboxylic acid ester in square lithium-ion batteries, and adjusting the electrolyte and battery design parameters, the problem of heat loss caused by square lithium-ion batteries is solved, and high energy density, fast charging capability and safety performance are achieved.
Patent Information
- Application Number
- CN202510323281.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-19
AI Technical Summary
Existing square lithium-ion batteries are prone to cause the problem of heat loss.
By adding excellent positive and negative electrode film forming additives (first additives) and short-chain carboxylic acid ester as non-aqueous organic solvents to the electrolyte, and by adjusting the mass percentage content of the first additive in the non-aqueous electrolyte, the mass percentage content of the short-chain carboxylic acid ester, the porosity of the negative electrode material layer and the group margin of the battery, the safety factor of the battery is defined so that it is within the range of 0.16≤σ≤1.35.
The square lithium-ion battery has a high energy density, high fast charging capability and high safety performance, reducing the risk of thermal runaway.
Smart Images

Figure QLYQS_1 
Figure QLYQS_3 
Figure QLYQS_4
Abstract
Description
Technical Field
[0001] The invention belongs to the field of secondary lithium ion batteries, and in particular relates to a square lithium ion battery. Background Art
[0002] Lithium-ion batteries have significant advantages such as high energy density, long cycle life, and no memory effect.
[0003] In recent years, new energy vehicles have put forward increasingly higher requirements for driving range and fast charging, which has also driven battery cell manufacturers to develop lithium-ion power batteries that take into account both energy density and fast charging performance requirements.
[0004] Phosphate batteries have a continuously increasing market share in the new energy vehicle sector due to their relatively good safety performance, long cycle life, low cost and other significant advantages.
[0005] However, phosphate materials themselves have poor kinetic properties, resulting in relatively poor fast charging capabilities of the battery.
[0006] In order to improve the fast charging performance of phosphate batteries, low-impedance additives can be added to the electrolyte end to reduce the interfacial impedance of the electrode; low-viscosity solvents can be used to improve the mass transfer capacity of the electrolyte and other methods to improve the fast charging performance of phosphate batteries, but this strategy will sacrifice the high-temperature performance of the battery and further cause thermal runaway. Summary of the invention
[0007] Based on this, the purpose of the present invention is to provide a square lithium-ion battery to solve the problem that square batteries in the prior art are prone to thermal runaway.
[0008] To achieve the above object, the present invention adopts the following technical solution.
[0009] The present invention provides a square lithium-ion battery, comprising a battery housing and a battery core assembly and a non-aqueous electrolyte contained in the battery housing, wherein the battery core assembly comprises a positive electrode sheet, a negative electrode sheet and a separator; The negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer disposed on the negative electrode current collector; The non-aqueous electrolyte includes a first additive, a lithium salt and a non-aqueous organic solvent, wherein the first additive includes at least one of the following compounds: ; The non-aqueous organic solvent includes a short-chain carboxylic acid ester having 2 to 5 carbon atoms, and the short-chain carboxylic acid ester includes at least one of ethyl acetate, ethyl propionate or methyl acetate; The square lithium-ion battery meets the following conditions: Safety Factor , satisfying 0.16≤σ≤1.35, 0.01≤a≤2, 24≤b≤56, 10≤c≤40, 85≤d≤93; Wherein, a is the mass percentage of the first additive in the non-aqueous electrolyte, in units of %; b is the mass percentage of short-chain carboxylic acid ester in the non-aqueous electrolyte, unit is %; c is the porosity of the negative electrode material layer, unit is %; d is the group margin of the square lithium-ion battery cell, in %.
[0010] The risk of thermal runaway of lithium-ion batteries stems from the exothermic reaction inside the battery. Lithium-ion batteries will still generate Joule heat during normal charging and discharging. As the temperature inside the battery gradually increases, the chemical properties of the materials inside the battery become more active.
[0011] The development process of thermal runaway mainly goes through the steps of decomposition of interface film, collapse of diaphragm, large-scale internal short circuit, reaction between electrode and electrolyte, and combustion of electrolyte.
[0012] When the decomposition of the interfacial film reaches a certain level, the positive and negative electrodes come into direct contact with the electrolyte and react, continuously increasing heat release.
[0013] Lithium salts (such as LiPF6) also decompose more easily under high temperature and high voltage conditions, which further promotes heat generation.
[0014] All of these reactions will increase the pressure and temperature inside the battery, bringing serious risk of thermal runaway.
[0015] Considering the initial stage of thermal runaway, constructing a SEI with good thermal stability is an effective means to reduce the risk of battery thermal runaway.
[0016] In the square lithium-ion battery provided in the present invention, at least one of compounds 1 to 5 is used as the first additive, and a short-chain carboxylic acid ester is used as the non-aqueous organic solvent. After extensive research, the inventors found that the safety factor of the square lithium-ion battery is defined by the mass percentage a of the first additive in the non-aqueous electrolyte, the mass percentage b of the non-aqueous organic solvent, the porosity c of the negative electrode material layer in the square lithium-ion battery, and the group margin d of the battery cell in the square lithium-ion battery. , and satisfying 0.16≤σ≤1.35, 0.01≤a≤2, 24≤b≤56, 10≤c≤40, 85≤d≤93, the square battery can have both high energy density and high safety performance.
[0017] As a non-aqueous organic solvent, short-chain carboxylic acid esters have strong polarity and can provide higher conductivity, while having lower viscosity and freezing point, which can significantly improve the fast charging capability of the battery, but will deteriorate the high temperature performance and further cause thermal runaway. To solve this problem, on the one hand, introducing excellent positive and negative electrode film-forming additives into the electrolyte can form a protective film with excellent thermal stability on the surface of the positive and negative electrodes to prevent corrosion and oxidation of the electrode materials at high temperatures, reduce the continuous increase in temperature during the charging and discharging process, and thus reduce the risk of thermal runaway; on the other hand, by controlling the group margin of the battery and the porosity of the negative electrode material layer, the heat generated by the battery during the charging and discharging process has enough space to be dissipated and conducted in time.
[0018] In general, electrolyte additives, solvents and various parameters of battery design jointly affect the comprehensive performance of the battery. The first additive can provide an interface film with excellent thermal stability, and the higher the content, the higher the safety performance of the generated interface film, that is, there is a positive correlation between the safety performance of the battery and the content of the first additive.
[0019] However, if the content of the first additive is too high, the battery interface impedance will increase simultaneously, which is not conducive to the fast charging performance of the battery.
[0020] The appropriate content of short-chain carboxylates can avoid the negative effect of increased impedance of the first additive. By introducing short-chain carboxylates into the electrolyte, the conductivity of the electrolyte is increased, further improving the fast charging performance of the battery while taking into account the high group margin of the battery cell.
[0021] However, short-chain carboxylates themselves have a low flash point and low chemical stability, and are easily decomposed at high temperatures, increasing the risk of thermal runaway. From the perspective of compatibility between electrolytes and positive and negative electrode materials, a stronger protective effect is needed to avoid the degradation of battery safety performance by short-chain carboxylate solvents.
[0022] Furthermore, suitable negative electrode porosity can ensure good wettability of the electrolyte, help the additives form a uniform interface film at the negative electrode interface, and at the same time take into account the problem of difficulty in the electrolyte infiltrating the battery cell after the battery cell group margin is increased. The larger the porosity, the more conducive it is to heat dissipation, and it will also consume more of the first additive to form a film at the negative electrode.
[0023] Taking into account the impact of increasing the first additive content and the negative electrode porosity on battery performance, as well as the mutual influence of increasing the short-chain carboxylate content in the electrolyte and the battery group margin, by defining the battery's safety factor σ between 0.16 and 1.35, the synergistic effect among the first additive, short-chain carboxylate solvent, negative electrode porosity and battery group margin design can be fully utilized, so that the square battery has high energy density, high fast charging capability and high safety performance.
[0024] Specifically, the safety factor σ is selected from 0.16, 0.17, 0.18, 0.19, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.15, 1.2, 1.25, 1.31, 1.35 or a range consisting of any two of these values.
[0025] Preferably, the safety factor σ is selected from 0.2 to 1.0.
[0026] The first additive is an excellent positive and negative electrode film-forming additive. During the first charge and discharge process of the battery, it can form a uniform interface film with moderate thickness and excellent thermal stability on the surface of the positive and negative electrodes, thereby inhibiting the temperature rise of the battery during the charge and discharge process.
[0027] When the mass percentage a% of the first additive in the non-aqueous electrolyte is too small, a dense interface film that completely covers the surface of the negative electrode cannot be generated, and the positive and negative electrode interfaces cannot be effectively protected; when the mass percentage a% of the first additive is too high, the generated interface film is thicker, and the interface impedance of the battery cell increases synchronously, which is not only not conducive to the rate performance of the battery, but also generates more Joule heat.
[0028] Specifically, the mass percentage a% of the first additive in the non-aqueous electrolyte is 0.01%, 0.03%, 0.05%, 0.07%, 0.09%, 0.1%, 0.3%, 0.3%, 0.5%, 0.7%, 0.9%, 1%, 1.3%, 1.5%, 1.7%, 1.9%, 2% or a range consisting of any two of these values.
[0029] Preferably, the mass percentage a% of the first additive in the non-aqueous electrolyte is 0.1%-1%.
[0030] In the non-aqueous electrolyte, short-chain carboxylates, as non-aqueous organic solvents, can avoid the negative effect of increased impedance of the first additive. Short-chain carboxylates have strong polarity and can provide higher conductivity, while having lower viscosity and freezing point, which can significantly improve the fast charging capability of the battery. If the mass percentage b% of the short-chain carboxylates is too low, it will be difficult for the electrolyte to wet the battery cell. If the mass percentage b% of the short-chain carboxylates is too high, although the electrolyte can easily wet the battery cell, the energy density of the battery cell is reduced, which will increase the risk of thermal runaway.
[0031] Specifically, the mass percentage b% of short-chain carboxylates in the non-aqueous electrolyte is 24%, 26%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 54%, 55%, 56% or a range consisting of any two of these values; preferably, the mass percentage b% of short-chain carboxylates in the non-aqueous electrolyte is 30%~50%.
[0032] Specifically, in some embodiments of the present invention, the porosity c% of the negative electrode material layer of the square lithium-ion battery is 10% to 40%.
[0033] If the negative electrode porosity is too low, the heat generated by the battery charging and discharging is difficult to dissipate and conduct; conversely, if the negative electrode porosity is too high, the contact between the negative electrode active material particles is reduced, the battery energy density decreases, and the wettability of the electrolyte also decreases.
[0034] By controlling the negative electrode porosity between 10≤c≤40, good safety performance and high energy density can be achieved.
[0035] Specifically, the porosity c% of the negative electrode material layer of the square lithium ion battery is 10%, 12%, 15%, 18%, 20%, 21%, 23%, 25%, 27%, 29%, 30%, 31%, 33%, 35%, 38%, 40% or a range consisting of any two of these values; preferably, the porosity c% of the negative electrode material layer of the square lithium ion battery is 15%~30%.
[0036] For prismatic batteries, the higher the battery group margin, the greater the risk of thermal runaway.
[0037] On the contrary, if the battery group margin is too low, it will be difficult to meet the requirements of high energy density of the battery.
[0038] The group margin of a battery refers to the ratio of the size of the battery cell assembly to the internal space size of the battery casing, also known as the "filling rate".
[0039] In some embodiments of the present invention, the group margin d% of the square lithium-ion battery is 85% to 93%, which can take into account both the battery energy density and safety performance to a certain extent.
[0040] The higher the battery group margin, the more difficult it is for the electrolyte to penetrate the entire battery cell when the battery is filled, resulting in difficulty in filling the battery. This can increase its energy density, but the heat generated by the battery during the charging and discharging process is difficult to conduct, increasing the risk of thermal runaway. Conversely, if the battery group margin is too low, it will be difficult to meet the battery's high energy density requirements.
[0041] Specifically, the group margin d% of the square lithium-ion battery is 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93% or a range consisting of any two of these values; preferably, the group margin d% of the square lithium-ion battery is 88%~92%.
[0042] Specifically, in some embodiments of the present invention, the test can be performed by measuring the thickness d1 of the battery cell and the thickness d2 of the inner space of the battery casing, and the group margin d% of the battery is = d1 / d2×100%.
[0043] Specifically, in some embodiments of the present invention, the selected carboxylate contains only a main chain, and the number of carbon atoms in the main chain is ≤5. The shorter the main chain of the carboxylate, the higher the conductivity and the lower the viscosity, which is more conducive to improving the conductivity and wettability of the electrolyte.
[0044] When the number of carbon atoms in the main chain exceeds 5, its viscosity and conductivity no longer have obvious advantages compared with chain carbonates, and it is difficult to meet the requirements of high conductivity and low viscosity.
[0045] Applying it in the battery system can significantly improve the battery's fast charging capability, but it will also deteriorate the high-temperature performance and further cause thermal runaway.
[0046] In some preferred embodiments of the present invention, the short-chain carboxylic acid ester comprises at least ethyl acetate.
[0047] Compared with other carboxylic acid ester compounds, ethyl acetate not only has a lower viscosity, which can reduce the resistance to the movement of lithium ions and help improve the ionic conductivity of the electrolyte, but also helps stabilize the positive electrode structure. Therefore, while improving the fast charging performance of lithium-ion batteries, it can also improve its high-temperature performance, thereby improving the overall performance of electrochemical devices.
[0048] Specifically, in some embodiments of the present invention, the non-aqueous electrolyte further includes an auxiliary additive, and the auxiliary additive includes at least one of cyclic sulfate compounds, sultone compounds, cyclic carbonate compounds, phosphate compounds, borate compounds and nitrile compounds.
[0049] In some preferred embodiments, the cyclic sulfate ester compound includes at least one of 4-methylvinyl sulfate, vinyl sulfate, and propylene sulfate.
[0050] In some preferred embodiments, the sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, and propenyl-1,3-sultone.
[0051] In some preferred embodiments, the cyclic carbonate compound includes at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, bisfluoroethylene carbonate and the compound shown in the following structural formula 1: ; In the structural formula 1 shown, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group.
[0052] In some preferred embodiments, the compound represented by structural formula 1 includes at least one of the compounds represented by compounds 1-1 to 1-6 below: .
[0053] In some preferred embodiments, the phosphate compound includes at least one of the compounds shown in the following structural formula 2: ; In the structural formula 2, R 31 , R 32 , R 33 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, a halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number of 1 to 3; more preferably, the compound shown in the structural formula 2 includes at least one of tris(trimethylsilane) phosphate, tris(triethylsilane) phosphate, tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate and diallyl hexafluoroisopropyl phosphate.
[0054] In some preferred embodiments, the borate ester compound includes at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate.
[0055] In some preferred embodiments, the nitrile compound includes at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile.
[0056] Specifically, in some embodiments of the present invention, based on the total mass of the non-aqueous electrolyte being 100%, the content of the auxiliary additive is 0.01% to 10%.
[0057] Preferably, the content is 0.1% to 5%.
[0058] More preferably, the content is 0.1% to 2%.
[0059] Specifically, the content of any optional substance in the auxiliary additives can be 0.01%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5% or a range consisting of any two of these values.
[0060] Specifically, in some embodiments of the present invention, the lithium salt includes LiPF6, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, LiPO2F2, LiBF4, LiBOB, LiSbF6, LiAsF6, LiCF3SO3, LiDFOB, LiDFOP, LiN(SO2CF3)2, LiC(SO2CF3)3, LiN(SO2C2F5)2, LiCl, LiBr, LiI, LiClO4, LiB 10 Cl 10 , LiAlCl4, lithium chloroborane, and lithium tetraphenylborate.
[0061] Specifically, in some embodiments of the present invention, the positive electrode sheet includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, the positive electrode active material includes a phosphate material; the phosphate material includes lithium iron phosphate and lithium manganese iron phosphate.
[0062] More specifically, the phosphate materials include LiFePO4, LiFe 0.4 Mn 0.6 PO4、LiFe 0.3 Mn 0.7 PO4、LiFe 0.2 Mn 0.8 PO4、LiFe 0.6 Mn 0.4 PO4、LiFe 0.8 Mn 0.2 PO4、LiFe 0.1 Mn 0.9 One or more of PO4.
[0063] Specifically, in some embodiments of the present invention, the positive electrode sheet further includes a positive electrode current collector, and the positive electrode material layer is disposed on the surface of the positive electrode current collector.
[0064] The positive electrode current collector includes a metal material that can conduct electrons.
[0065] Preferably, the positive electrode current collector includes one or more of aluminum, nickel, tin, copper, and stainless steel.
[0066] Specifically, in some embodiments of the present invention, the positive electrode sheet further includes a positive electrode binder and a positive electrode conductor.
[0067] The positive electrode binder includes polyvinylidene fluoride, copolymers of vinylidene fluoride, polytetrafluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ether, copolymers of ethylene-tetrafluoroethylene, copolymers of vinylidene fluoride-tetrafluoroethylene, copolymers of vinylidene fluoride-trifluoroethylene, copolymers of vinylidene fluoride-trichloroethylene, copolymers of vinylidene fluoride-fluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, thermoplastic resins such as polyethylene and polypropylene; acrylic resin; and one or more of styrene butadiene rubber.
[0068] The positive electrode conductive agent includes one or more of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0069] Specifically, in some embodiments of the present invention, the negative electrode sheet includes a negative electrode material layer; the negative electrode material layer includes a negative electrode active material; the negative electrode active material includes at least one of a silicon-based negative electrode and a carbon-based negative electrode; the silicon-based negative electrode includes at least one of a silicon material, a silicon oxide, a silicon-carbon composite material and a silicon alloy material.
[0070] Preferably, the silicon material is nano-silicon material.
[0071] Preferably, the silicon oxide material is SiO x Materials, where 0≤x<2.
[0072] Preferably, the silicon-carbon material is: a silicon-based material containing silicon and carbon material, and / or a silicon-based material containing SiO y and a silicon-based material of a carbon material, wherein 0≤y<2.
[0073] Preferably, the silicon alloy material is a Mg2Si alloy material and / or a Fe2Si alloy material.
[0074] The carbon material is selected from one or more of artificial graphite, natural graphite, composite graphite, graphene, hard carbon, soft carbon, and mesophase carbon microspheres; preferably, the carbon material is an artificial graphite material.
[0075] Specifically, in some embodiments of the present invention, the carbon-based negative electrode includes at least one of graphite, hard carbon, soft carbon, graphene, and mesophase carbon microbeads.
[0076] The silicon-based material is selected from one or more of silicon materials, silicon oxide materials, silicon-carbon materials and silicon alloy materials.
[0077] Specifically, in some embodiments of the present invention, the negative electrode material layer further includes a negative electrode binder, a negative electrode conductor and a negative electrode current collector.
[0078] The material of the negative electrode current collector may be the same as that of the positive electrode current collector, and will not be described in detail herein.
[0079] The negative electrode binder and the negative electrode conductor may be the same as the positive electrode binder and the positive electrode conductor, respectively, and will not be described in detail herein.
[0080] Specifically, in some embodiments of the present invention, the square lithium-ion battery further includes a diaphragm, and the diaphragm is located between the positive electrode sheet and the negative electrode sheet.
[0081] The diaphragm is an existing conventional diaphragm, selected from one or more of a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, and an inorganic-organic composite diaphragm.
[0082] For example, a single-layer polypropylene (PP) separator, a single-layer polyethylene (PE) separator, a double-layer PP / PE separator, a double-layer PP / PP separator or a triple-layer PP / PE / PP separator.
[0083] Specifically, in some embodiments of the present invention, the battery shell includes one selected from a steel shell, an aluminum shell, a polypropylene (PP) plastic shell, a polycarbonate (PC) plastic shell or a carbon fiber composite material shell.
[0084] The square lithium-ion battery provided by the present invention takes into account the aspects of electrolyte additives, solvents and battery design, adds a first additive and a short-chain carboxylic acid ester to a non-aqueous electrolyte, and controls the safety factor σ by adjusting the relationship between the mass percentage a of the first additive in the non-aqueous electrolyte, the mass percentage b of the short-chain carboxylic acid ester, the porosity c of the negative electrode material layer, and the group margin d of the square lithium-ion battery cell. The synergistic effect between the first additive, the short-chain carboxylic acid ester solvent, the negative electrode porosity and the group margin design of the battery can be fully utilized, so that the square battery has high energy density, high fast charging capability and high safety performance.
[0085] The reason is speculated to be: using short-chain carboxylates as non-aqueous organic solvents has a strong polarity and can provide higher conductivity, while having lower viscosity and freezing point, which can significantly improve the fast charging capability of the battery, but at the same time deteriorate the high-temperature performance and further cause thermal runaway.
[0086] To solve this problem, on the one hand, introducing an excellent positive and negative electrode film-forming additive first additive into the electrolyte can form a protective film with excellent thermal stability on the surface of the positive and negative electrodes to prevent corrosion and oxidation of the electrode material at high temperatures, reduce the continuous increase in temperature during the charging and discharging process, and thus reduce the risk of thermal runaway; on the other hand, by controlling the battery group margin and the porosity of the negative electrode material layer, the heat generated by the battery during the charging and discharging process has enough space to dissipate and be dissipated and conducted in time. DETAILED DESCRIPTION
[0087] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0088] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the protection scope of the present invention.
[0089] Example 1 The method for preparing a square lithium-ion battery in this embodiment comprises the following steps: (1) Positive electrode preparation: Lithium iron phosphate, conductive carbon black Super-P, and binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 96:2:2, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry.
[0090] The positive electrode slurry is evenly coated on both sides of the aluminum foil current collector, and after drying, rolling, vacuum drying, and welding aluminum lead wires with an ultrasonic welder, a positive electrode sheet is obtained.
[0091] (2) Negative electrode preparation: The negative electrode active material artificial graphite, conductive carbon black Super-P, binder styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) were mixed in a mass ratio of 95:1:1.5:2.5.
[0092] Then they were dispersed in deionized water to obtain negative electrode slurry.
[0093] The negative electrode slurry is coated on both sides of the copper foil, and after drying, rolling, vacuum drying, and welding nickel lead wires with an ultrasonic welder, a negative electrode sheet is obtained.
[0094] The porosity of the negative electrode material layer is 20%.
[0095] (3) Preparation of non-aqueous electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and ethyl acetate (EA) are mixed, and the first additive (compound 1), vinylene carbonate (VC) and fluoroethylene carbonate (FEC) are added thereto, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1.05 mol / L.
[0096] Based on the total weight of the non-aqueous electrolyte being 100%, the content of ethyl acetate (EA) is 50%, the content of compound 1 is 0.5%, the content of VC is 2%, and the content of FEC is 0.5%.
[0097] (4) Diaphragm preparation: A three-layer isolation membrane made of polypropylene, polyethylene and polypropylene was used with a thickness of 20 μm.
[0098] (5) Battery assembly: A three-layer separator with a thickness of 20 μm is placed between the positive plate and the negative plate, and then the sandwich structure consisting of the positive plate, the negative plate and the separator is wound or stacked, and then the battery cell is placed in a square casing, and the casing is sealed after welding the pole ears to obtain a battery cell to be injected with liquid; the electrolyte prepared above is cut and injected into the battery cell, and the battery cell is sealed after standing for 1 hour. The sealed battery is aged at 45° C. for 48 hours.
[0099] Then, the conventional formation of the first charge is carried out according to the following steps: 0.05C constant current charging for 2 hours, 0.1C constant current charging for 1 hour, and 0.2C constant current charging for 1 hour.
[0100] The group margin of the square lithium-ion battery cell obtained in this embodiment is 91%.
[0101] Example 2 to Example 27 and Comparative Example 1 to Comparative Example 17 This embodiment and comparative example are used to compare and illustrate the square lithium-ion battery disclosed in the present invention, including most of the operating steps in the above-mentioned embodiment 1, and the differences are: the composition of the non-aqueous electrolyte and the content of each component, the porosity of the negative electrode material, the group margin and the safety factor σ of the square lithium-ion battery cell, as shown in Tables 1 to 4.
[0102] The square lithium-ion batteries prepared in each embodiment and comparative example were subjected to the following performance tests: (1) 150℃ hot box test: The fully charged battery is placed in the GX-3020-BL40 thermal shock test chamber. The heat chamber works according to the set program "heating from 25°C to 150°C at 5°C / min and maintaining for 30 minutes". At the same time, the temperature channel and voltage channel of the "data acquisition instrument" panel begin to record real-time data on the battery cell surface.
[0103] Hot box pass rate test: Before the test, the battery is charged to a constant current and voltage of 3.65 V at a current of 0.5C and a cut-off current of 0.05C. After charging, it is left to stand for 4 hours.
[0104] The fully charged battery was placed in a GX-3020-BL40 thermal shock test chamber, and the heat chamber operated according to the set program "raising the temperature from 25°C to 150°C at 5°C / min and maintaining it for 30 minutes".
[0105] If the battery opens, catches fire or explodes, it fails the test; if the battery does not open, catch fire or explode, it passes the test.
[0106] Twenty batteries were tested for each embodiment and comparative example, and the passing rate = the number of batteries passed / 20.
[0107] (2) Rate charging high temperature cycle performance test: At 45°C, the battery was charged to 3.65V at 4C constant current and voltage, with a cut-off current of 0.05C, and then discharged to 2.5V at 1C constant current.
[0108] The first discharge capacity and the 1000th discharge capacity were recorded.
[0109] The capacity retention rate of high temperature cycle is calculated as follows: Capacity retention rate (%) = 1000th discharge capacity / 1st discharge capacity × 100%.
[0110] Test Results As shown in Table 1, various parameters of the square lithium-ion batteries prepared in Examples 1 to 17 and Comparative Examples 3 to 14 are shown; the differences between Examples 2 to 17 and Comparative Examples 3 to 14 and Example 1 are the relevant parameters in Table 1.
[0111] Table 1 Group First additive content a / % Solvent content b / % Porosity of negative electrode material layer c / % Group margin d / % of prismatic lithium-ion batteries Safety factor σ 150℃ hot box pass rate 45℃ 4C / 1C cycle 1000 cycles capacity retention rate / % Example 1 0.5 50 20 91 0.44 20 / 20 92.1 Example 2 0.1 35 15 88 0.30 20 / 20 89.9 Example 3 0.9 50 29 92 0.81 19 / 20 91.5 Example 4 0.3 37 27 89 0.61 20 / 20 90.1 Example 5 1 45 19 92 0.59 20 / 20 91.3 Example 6 0.01 36 12 89 0.21 19 / 20 83.6 Example 7 0.6 40 15 90 0.40 20 / 20 89.7 Example 8 0.2 42 30 88 0.59 20 / 20 90.1 Example 9 0.05 48 10 88 0.16 17 / 20 89.3 Example 10 0.09 52 23 90 0.37 19 / 20 89.7 Embodiment 11 1.2 54 32 92 1.00 19 / 20 87.4 Example 12 1 50 30 93 0.88 19 / 20 88.5 Embodiment 13 1.3 28 28 93 1.26 17 / 20 85.6 Embodiment 14 1.8 56 17 89 0.67 18 / 20 87.9 Embodiment 15 2 35 15 85 0.83 20 / 20 84.3 Example 16 0.8 24 33 85 1.32 17 / 20 83.9 Embodiment 17 0.05 56 40 93 0.58 18 / 20 83.5 Comparative Example 3 0 50 10 93 0.22 5 / 20 82.2 Comparative Example 4 0.5 0 10 93 0 10 / 20 73.1 Comparative Example 5 2.1 50 15 90 0.69 13 / 20 83.1 Comparative Example 6 0.008 50 15 90 0.23 8 / 20 82.6 Comparative Example 7 0.5 60 17 90 0.35 9 / 20 83.3 Comparative Example 8 0.5 20 17 90 0.60 10 / 20 79.9 Comparative Example 9 0.5 50 42 90 0.94 14 / 20 76.8 Comparative Example 10 0.5 50 8 90 0.18 8 / 20 79.5 Comparative Example 11 0.8 50 20 94 0.53 12 / 20 82.9 Comparative Example 12 0.8 50 20 83 0.56 13 / 20 83.4 Comparative Example 13 1.5 45 36 93 1.39 10 / 20 83.1 Comparative Example 14 0.01 56 10 85 0.15 6 / 20 82.3 It can be seen from the test results of Examples 1 to 17 and Comparative Examples 3 to 14 that the square lithium-ion battery provided in the present invention uses at least one of Compounds 1 to 5 as the first additive and a short-chain carboxylic acid ester as the non-aqueous organic solvent; and the safety factor of the lithium-ion battery is defined by limiting the mass percentage a of the first additive in the non-aqueous electrolyte, the mass percentage b of the non-aqueous organic solvent, the porosity c of the negative electrode material layer in the square lithium-ion battery, and the group margin d of the battery cell in the square lithium-ion battery. , and satisfying 0.16≤σ≤1.35, 0.01≤a≤2, 30≤b≤60, 10≤c≤40, 85≤d≤93, the square battery can have both high safety performance and fast charging performance.
[0112] It can be seen from the test results of Example 1 and Comparative Examples 3 to 14 that when any one of the mass percentage a of the first additive in the non-aqueous electrolyte, the mass percentage b of the non-aqueous organic solvent, the porosity c of the negative electrode material layer in the square lithium-ion battery, and the group margin d of the battery cell in the square lithium-ion battery does not meet the range or the value of the safety factor σ of the lithium-ion battery defined by the above parameters is too large or too small, it will not be possible to ensure that a protective film with excellent thermal stability is formed on the positive and negative electrode surfaces of the battery, which will cause corrosion and oxidation of the electrode material or when the battery is in the process of charging and discharging, there is not enough space to dissipate and conduct heat, thereby causing the battery to heat up and run away.
[0113] When the mass percentage a of the first additive, the mass percentage b of the non-aqueous organic solvent, the porosity c of the negative electrode material layer in the square lithium-ion battery, the group margin d and the safety factor σ of the battery cell in the square lithium-ion battery further satisfy 0.2≤σ≤1.0, 0.1≤a≤1, 30≤b≤50, 15≤c≤30, 88≤d≤92, the square battery has high energy density, high fast charging capability and high safety performance.
[0114] Within this range, the first additive can provide an interface film with excellent thermal stability, and an appropriate content of carboxylic acid ester can avoid the negative effect of increased impedance of the additive while taking into account the group margin of the battery cell.
[0115] Furthermore, within this range, the negative electrode porosity can ensure good wettability of the electrolyte, help the first additive to form a uniform interface film at the negative electrode interface, and at the same time take into account the problem of difficulty in electrolyte wetting the battery cell after the battery cell group margin is increased.
[0116] By comprehensively considering the mutual influence of various design parameters and controlling the battery's safety factor σ between 0.16 and 1.35, the synergistic effect among additives, solvents, negative electrode materials and cell group margin design can be fully utilized, so that the square battery has high energy density, high fast charging capability and high safety performance.
[0117] It can generate an interface film with excellent thermal stability on the surface of the positive and negative electrodes of the battery, which can better prevent the corrosion and oxidation of the electrode material at high temperatures, and allow the battery to have sufficient space to dissipate heat during the charging and discharging process, so that the heat generated can be dissipated and conducted in time.
[0118] Table 2 shows various parameters of the square lithium-ion batteries prepared in Example 1 and Example 18 to Example 19; the difference between Example 18 to Example 19 and Example 1 lies in the relevant parameters in Table 2.
[0119] Table 2 Group The first additive type 150℃ hot box pass rate 45℃ 4C / 1C cycle 1000 cycles capacity retention rate / % Example 1 Compound 1 20 / 20 92.1 Embodiment 18 Compound 2 20 / 20 91.8 Embodiment 19 Compound 3 20 / 20 91.5 Embodiment 20 Compound 4 20 / 20 92.0 Embodiment 21 Compound 5 20 / 20 91.7 It can be seen from the measurement results in Table 2 that when the mass percentage a of the first additive in the non-aqueous electrolyte, the mass percentage b of the non-aqueous organic solvent, the porosity c of the negative electrode material layer in the square lithium-ion battery, the group margin d of the battery cell in the square lithium-ion battery and the safety factor σ of the lithium-ion battery meet the relevant requirements, using any one of Compounds 1 to 5 as the first additive can prevent the electrode material from corrosion and oxidation at high temperatures, and can allow the battery to dissipate heat in sufficient space during the charging and discharging process, so that the generated heat can be dissipated and conducted in time, so that the square battery has high energy density, high fast charging capability and high safety performance.
[0120] It is shown that the battery system of the present invention is universally applicable to different first additives.
[0121] Table 3 shows various parameters of the lithium-ion batteries prepared in Example 1 and Examples 21 to 26 and Comparative Examples 15 to 17; the differences between Examples 21 to 26 and Comparative Examples 15 to 17 and Example 1 are the relevant parameters in Table 3.
[0122] Table 3 Group Solvent type 150℃ hot box pass rate 45℃ 4C / 1C cycle 1000 cycles capacity retention rate / % Example 1 Ethyl acetate 20 / 20 92.1 Embodiment 21 Ethyl propionate 20 / 20 91.5 Embodiment 22 Methyl acetate 18 / 20 92.5 Embodiment 23 Ethyl acetate: ethyl propionate = 1:1 20 / 20 91.8 Embodiment 24 Ethyl acetate: methyl acetate = 1:1 19 / 20 92.3 Embodiment 25 Ethyl propionate: methyl acetate = 1:1 20 / 20 92.0 Embodiment 26 Ethyl acetate: ethyl propionate: methyl acetate = 1:1:1 20 / 20 91.9 Comparative Example 15 Ethyl butyrate 16 / 20 95.4 Comparative Example 16 Propyl Propionate 16 / 20 94.8 Comparative Example 17 Butyl Propionate 15 / 20 93.9 It can be seen from Table 3 that when the mass percentage a of the first additive in the non-aqueous electrolyte, the mass percentage b of the non-aqueous organic solvent, the porosity c of the negative electrode material layer in the square lithium-ion battery, the group margin d of the battery cell in the square lithium-ion battery and the safety factor σ of the lithium-ion battery meet the relevant requirements, using different short-chain carboxylates as solvents can prevent the electrode material from corrosion and oxidation at high temperatures, and allow the battery to have sufficient space to dissipate heat during the charging and discharging process, so that the generated heat can be dissipated and conducted in time, so that the square battery has high energy density, high fast charging capability and high safety performance.
[0123] It is demonstrated that the battery system of the present invention is universally applicable to different solvents.
[0124] From the results of Example 1, Example 21 to Example 22 and Comparative Examples 15 to 17, it can be seen that when long-chain carboxylates are used as solvents, the viscosity and conductivity of long-chain carboxylates no longer have obvious advantages over linear carbonates, and it is difficult to meet the requirements of high conductivity and low viscosity. Although the use of long-chain carboxylates can significantly improve the fast charging capability of the battery, the high temperature performance is deteriorated, further causing thermal runaway.
[0125] Table 4 shows the various parameters of the lithium ion batteries prepared in Example 1, Example 27 to Example 28, and Comparative Example 1 to Example 2; the differences between Example 27 to Example 28, and Comparative Example 1 to Example 2 and Example 1 are the relevant parameters in Table 4.
[0126] Table 4 Group First additive content a% Type and content of auxiliary additives 150℃ hot box pass rate 45℃ 4C / 1C cycle 1000 cycles capacity retention rate / % Example 1 0.5 / 20 / 20 92.1 Embodiment 27 0.5 0.5%MMDS 20 / 20 93.4 Embodiment 28 0.5 0.5%DTD 20 / 20 92.5 Comparative Example 1 0 0.5%DTD 14 / 20 82.2 Comparative Example 2 0 0.5%MMDS 14 / 20 82.4 Note: “ / ” in the table means there is no such item.
[0127] It can be seen from Table 4 that when the mass percentage a of the first additive in the non-aqueous electrolyte, the mass percentage b of the non-aqueous organic solvent, the porosity c of the negative electrode material layer in the square lithium-ion battery, the group margin d of the battery cell in the square lithium-ion battery and the safety factor σ of the lithium-ion battery meet the relevant requirements, adding different types of auxiliary additives can prevent the electrode material from corrosion and oxidation at high temperatures, and can allow the battery to dissipate heat in sufficient space during the charging and discharging process, so that the generated heat can be dissipated and conducted in time, so that the square battery has high energy density, high fast charging capability and high safety performance.
[0128] If the first additive is not added and only the auxiliary additive is used, an interface film with excellent thermal stability cannot be formed, which is not conducive to the rate performance of the battery and will generate more Joule heat, increasing the risk of thermal runaway.
[0129] The above-mentioned embodiments only express several implementation modes of the present invention, and the description thereof is relatively specific and detailed, but it should not be understood as limiting the patent scope of the present invention.
[0130] It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all fall within the protection scope of the present invention.
[0131] Therefore, the protection scope of the patent for this invention shall be based on the attached claims.
Claims
1. A square lithium-ion battery, characterized in that: It comprises a battery housing, a battery core assembly and a non-aqueous electrolyte contained in the battery housing, wherein the battery core assembly comprises a positive electrode sheet, a negative electrode sheet and a separator; The negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer disposed on the negative electrode current collector; The non-aqueous electrolyte includes a first additive, a lithium salt and a non-aqueous organic solvent, wherein the first additive includes at least one of the following compounds: ; The non-aqueous organic solvent includes a short-chain carboxylic acid ester having 2 to 5 carbon atoms, and the short-chain carboxylic acid ester includes at least one of ethyl acetate, ethyl propionate or methyl acetate; The square lithium-ion battery meets the following conditions: Safety Factor , satisfying 0.16≤σ≤1.35, 0.01≤a≤2, 24≤b≤56, 10≤c≤40, 85≤d≤93; Wherein, a is the mass percentage of the first additive in the non-aqueous electrolyte, in units of %; b is the mass percentage of short-chain carboxylic acid ester in the non-aqueous electrolyte, unit is %; c is the porosity of the negative electrode material layer, unit is %; d is the group margin of the square lithium-ion battery, in %.
2. The square lithium-ion battery according to claim 1, characterized in that: The safety factor of the square lithium-ion battery satisfies: 0.2≤σ≤1.
0.
3. The square lithium-ion battery according to claim 1, characterized in that: The mass percentage a% of the first additive in the non-aqueous electrolyte is 0.1%-1%.
4. The square lithium-ion battery according to claim 1, characterized in that: The mass percentage b% of the short-chain carboxylic acid ester in the non-aqueous electrolyte is 30%-50%.
5. The square lithium-ion battery according to claim 1, characterized in that: The porosity c% of the negative electrode material layer is 15% to 30%.
6. The square lithium-ion battery according to claim 1, characterized in that: The group margin d% of the square lithium-ion battery is 88% to 92%.
7. The square lithium-ion battery according to claim 1, characterized in that: The non-aqueous electrolyte further includes an auxiliary additive, wherein the auxiliary additive includes at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, a borate compound and a nitrile compound; and / or, Based on the total mass of the non-aqueous electrolyte being 100%, the content of the auxiliary additive is 0.01% to 10%.
8. The square lithium-ion battery according to claim 7, characterized in that: The cyclic sulfate ester compound includes at least one of 4-methylvinyl sulfate, vinyl sulfate, and propylene sulfate; and / or, The sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone and propenyl-1,3-sultone; and / or, The cyclic carbonate compound includes at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, bisfluoroethylene carbonate and the compound shown in the following structural formula 1: ; In the structural formula 1 shown, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, a C1-C5 group; and / or, The phosphate compound includes at least one of the compounds shown in the following structural formula 2: ; In the structural formula 2, R 31 , R 32 , R 33 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, a halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number from 1 to 3; and / or, The borate compound includes at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate; and / or, The nitrile compound includes at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile.
9. The square lithium-ion battery according to claim 1, characterized in that: The non-aqueous organic solvent further comprises one or more of cyclic carbonates or linear carbonates; and / or, The cyclic carbonate includes one or more of vinylene carbonate, propylene carbonate, ethylene carbonate and butylene carbonate; and / or, The chain carbonate includes one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, methyl trifluoroethyl carbonate and bis(2,2,2-trifluoroethyl) carbonate.
10. The square lithium-ion battery according to claim 1, characterized in that: The positive electrode sheet comprises a positive electrode material layer, the positive electrode material layer comprises a positive electrode active material, and the positive electrode active material comprises a phosphate material; The negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes at least one of a silicon-based negative electrode and a silicon-carbon negative electrode.
Citation Information
Patent Citations
Lithium ion battery
CN115498268A
Secondary battery, battery module, battery pack, and electric device
CN116941087A
Lithium ion secondary battery
CN118738569A
Nonaqueous electrolytic solution and energy storage device using the same
US20170373348A1
Cited By
Prismatic lithium-ion battery
WO2026194378A1